2021
DOI: 10.1088/1742-6596/1760/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Train students’ science process skills and self-efficacy in online learning using the Scientific Critical Thinking (SCT) model assisted by google classroom and google meet

Abstract: Science process skills and self-efficacy need to be trained in students in chemistry learning activities at school. This will have a positive impact on students in facing and solving problems in their lives. The Scientific Critical Thinking (SCT) model is one of the models that can be used to implement learning. This research was conducted at SMAN 11 Banjarmasin, class XI MIPA 2, on the buffer solution’s material, assisted by google classroom and google meet. This study aims to determine (1) the improvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
1
5
0
4
Order By: Relevance
“…These findings are similar to the study by Juan et al (2018) which demonstrated that there was a positive relationship between self-efficacy and science achievement and suggested a need to also focus on noncognitive aspects to improve science achievement. Moreover, the study of Rusmansyah et al (2021) showed that there was a significant increase in students' self-efficacy and science process skills in doing practical activities athome assisted by Google Classroom and Google Meet applications.…”
Section: Students' Self-efficacy In the Context Of Home-based Biology...mentioning
confidence: 99%
“…These findings are similar to the study by Juan et al (2018) which demonstrated that there was a positive relationship between self-efficacy and science achievement and suggested a need to also focus on noncognitive aspects to improve science achievement. Moreover, the study of Rusmansyah et al (2021) showed that there was a significant increase in students' self-efficacy and science process skills in doing practical activities athome assisted by Google Classroom and Google Meet applications.…”
Section: Students' Self-efficacy In the Context Of Home-based Biology...mentioning
confidence: 99%
“…Some time ago, the school imposed an online learning system due to the covid-19 pandemic (Wiradinata et al, 2021). Students undertake learning activities through Google Classroom (Rusmansyah et al, 2021) and Microsoft Teams. The implementation of online learning inhibits teachers from applying learning to train PSS in students, so the application of PSS still needs to be improved.…”
Section: Teacher and Student Interviewmentioning
confidence: 99%
“…Tergambarkan dari data statistik deskriptif di atas menunjukkan bahwa rata-rata hasil belajar mahasiswa pada mata kuliah Metodologi Penelitian Kuantitatif menunjukkan hasil posttest lebih tinggi dibandingkan hasil pretest. Sejalan dengan penelitian yang dilakukan oleh Rusmansyah, Hayati, Winarti, & Rahmi (2021) menyatakan bahwa penelitian yang dilakukan pada siswa SMA mengalami kenaikan yang besar pada posttest setelah digunakan media Google Meet. Selain itu didukung pula oleh penelitian yang dilakukan oleh Muniroh, Rojanah, & Raharjo (2020) menyatakan bahwa hasil belajar siswa dengan menggunakan media aplikasi Google Meet lebih tinggi dibandingkan dengan hasil belajar siswa yang tidak menggunakan media aplikasi Google Meet.…”
Section: Pembahasanunclassified